An effective interests alignment mechanism or a tool to expropriate: A review of Malaysian ESOS adoption - Ghazali, Zahiruddin; Md. Taib, Fauziah (2011)
ESOS is theorised as a solution to bridge the interest of managers with owners of the firms particularly in setting where ownership is widely held. Modern corporations in developing countries are characterised by controlling shareholders who are also actively involve in the management of the firms. The resultant conflict of interests between majority and minority shareholders questions the suitability of ESOS in aligning their interests towards firms’ common goal. Findings from the study suggest that the usual determinants of ESOS adoption in the West do not hold in the environment of high ownership concentration. The post-adoption performance has not improved and there is no significant difference between adopting and non-adopting firms after controlling for size and industry. Nonetheless, there is evidence of better performance for adopting firms in terms of profitability albeit very weak in magnitude.